THE USE OF COOPERATIVE LEARNING IN IMPROVING STUDENTS' SKILL IN WRITING RECOUNT TEXT - Amalia Nur Aziza, - (2010)
The purposes of this research were to investigate whether cooperative learning improved students' skill in writing recount and how their responses towards the method. Cooperative learning was chosen as an alternative method in teaching writing because it could facilitate students to involve actively in learning process. Quasi-experimental design was employed in this research. The samples were two classes of tenth grade of a public senior high school in Bandung. The data was collected from administering writing test and questionnaire. The study revealed that cooperative learning improved students' writing skill. The result of independent t-test showed that the significance value was lower than level of significance (0.000 < 0.05). It indicated that H0 was rejected which meant there was a significant difference in posttest means between control and experimental groups after treatment. The normalized average gain value of the experimental group was higher than the control group that showed the use of cooperative learning was effective in improving students' skill in writing recount text. The results of questionnaire analysis also showed that students had positive responses toward the use of cooperative learning. Based on these findings, it is recommended that cooperative learning is used by English teachers in teaching writing.